Evidence of Guanidines Potential against Leishmania (Viannia) braziliensis: Exploring In Vitro Effectiveness, Toxicities and of Innate Immunity Response Effects - Luana Ribeiro dos Anjos; Vanessa Maria Rodrigues de Souza; Yasmim Alves Aires Machado; Vitor Moreira Partite; Mohammed Aufy; Geovane Dias Lopes; Christian Studenik; Carlos Roberto Alves; Gert Lubec; Eduardo Rene Perez Gonzalez; Klinger Antonio da Franca Rodrigues (Biomolecules, 2023)
Leishmaniasis is a complex group of infectious and parasitic diseases that afflict many thousands of individuals across five continents. Leishmaniasis treatment remains a challenge because it relies on drugsknown for their high toxicity and limited efficacy, making itimperative to identify new molecules that offer greater effectiveness and safety. This study sought to explore the impact of seven synthetic guanidine derivatives (LQOF-G1, LQOF-G2, LQOF-G6, LQOF-G7, LQOF-G32, LQOF-G35 and LQOF-G36) onthe parasite Leishmania (Viannia) braziliensis and in vitro macrophage infection by this parasite, as well as cytotoxic approaches in vitro models of mammalian host cells and tissues. The synthesized compounds showed purity ≥ 99.65% and effectively inhibited parasite growth. LQOF-G1 proved the most potent, yielding the best half-maximal inhibitory concentration (IC50) values against promastigotes (4.62 μmol/L), axenic amastigotes (4.27 μmol/L), and intracellular amastigotes (3.65 μmol/L). Notably, the antileishmanial activity of LQOF-G1, LQOF-G2, and LQOF-G6 was related to immunomodulatory effects, evidenced by alterations in TNF-α, IL-12, IL-10, nitric oxide (NO), and reactive oxygen species (ROS) levels in the supernatant of culture macrophages infected with L. (V.) braziliensis and coincubated with these compounds. LQOF-G2 and LQOF-G36 compounds exhibited vasodilator and spasmolytic effects at higher concentrations (≥100 μmol/L). Generally, LQOF-G1, LQOF-G2, and LQOF-G32 compounds were found to be nontoxic to assessed organs and cells. No toxic effects were observed in human cell lines, such as HEK-293, CaCo-2 and A549, at concentrations ≥ 500 μmol/L. Collectively, data have shown unequivocal evidence of the effectiveness of these compounds against L. (V.) braziliensis parasite, one of the causative agents of Tegumentary Leishmaniasis and Mucocutaneous Leishmaniasis in America.